2017
DOI: 10.1016/j.exppara.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma growth in vitro is dependent on exogenous tyrosine and is independent of AAH2 even in tyrosine-limiting conditions

Abstract: Toxoplasma gondii is an obligate intracellular parasite capable of infecting virtually all nucleated cell types in almost all warm-blooded animals. Interestingly, Toxoplasma has a relatively full repertoire of amino acid biosynthetic machinery, perhaps reflecting its broad host range and, consequently, its need to adapt to a wide array of amino acid resources. Although Toxoplasma has been shown to be auxotrophic for tryptophan and arginine, it has not previously been determined if Toxoplasma is also auxotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…WT and Δ apiAT5-3 parasites were grown in DMEM containing 0 – 2.5 mM L-Tyr. Growth of WT parasites in the absence of L-Tyr was severely impaired (Fig S8A), consistent with a previous study that indicated T. gondii parasites are auxotrophic for this amino acid (20). WT parasites grew normally in [L-Tyr] as low as 10 μM (Fig 8A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…WT and Δ apiAT5-3 parasites were grown in DMEM containing 0 – 2.5 mM L-Tyr. Growth of WT parasites in the absence of L-Tyr was severely impaired (Fig S8A), consistent with a previous study that indicated T. gondii parasites are auxotrophic for this amino acid (20). WT parasites grew normally in [L-Tyr] as low as 10 μM (Fig 8A).…”
Section: Resultssupporting
confidence: 92%
“…The evolution of apicomplexan ancestors from a free-living to an obligate parasitic life-style was associated with the loss of numerous biosynthetic pathways, including those for amino acid synthesis (23, 24). In particular, T. gondii is auxotrophic for many amino acids, including the aromatic amino acids L-Tyr, L-Phe and L-Trp ((5, 20, 21, 2527); this study). Parasites must scavenge essential amino acids from their environment, although, in the case of apicomplexan parasites, how they do so is poorly understood.…”
Section: Discussionmentioning
confidence: 90%
“…In infected cells, the important purine synthetic enzyme tetrahydrofolate synthase (MTHFD1) was upregulated compared to uninfected cells from 6 to 48 HPI (Table 1). PRPP Synthase (PRS1), which is Triplicate infected and uninfected dishes of HFFs were metabolically quenched and metabolites were extracted at 8 times points (1.5,3,6,9,12,24,36,and 48 HPI). Metabolomes were quantified using HPLC-MS and metabolites were identified with known standards.…”
Section: Nucleotide Synthesis Increasesmentioning
confidence: 99%
“…These central pathways are generally fueled by glucose or glutamine scavenged from the host cell. Other areas of metabolism, including amino acid, nucleotide, and lipid synthesis, are partially present but rely on host metabolism to provide certain metabolites, including arginine [10], tryptophan [11], tyrosine [12], purines [13] and cholesterol [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a eukaryote T. gondii possesses a complex metabolism with most of the major metabolic pathways complete, including the tricarboxylic acid (TCA) cycle, the pentose phosphate pathway (PPP), gluconeogenesis and glycolysis [6-13]. Other areas of metabolism, including amino acid and nucleotide synthesis, are partially present but rely on host metabolism to provide certain precursors and products [2-4,12,14]. T. gondii metabolism also contains unusual pathways for a eukaryote, including a fungal-like shikimate pathway for aromatic amino acid synthesis and an algal-like fatty acid synthesis II pathway [15-17].…”
Section: Introductionmentioning
confidence: 99%